Biopsy Confirmed Doxycycline Induced Gastric Mucosal Injury. (October 2022) - Gaulden, Hannah; Dungan, William; Romano, John; Willner, Ira
Doxycycline (DOX) is a tetracycline antibiotic that is prescribed for treating a variety of infections involving the skin, respiratory tract, and urogenital system. Adversely, esophageal mucosal injury due to DOX is well described; however, gastric mucosal injury is less commonly reported and may result in severe gastrointestinal hemorrhage and occasionally, perforation. In most reported cases of DOX-induced gastric lesions, patients are symptomatic upon presentation leading to endoscopic evaluation and diagnosis with biopsy. However, severe gastric insults may go unrecognized in rare cases of asymptomatic patients, increasing the risk of mortality.